Low risk of adenocarcinoma and high-grade dysplasia in patients with non-dysplastic Barrett's esophagus: Results from a cohort from a country with low esophageal adenocarcinoma incidence. Issue 3 (June 2016) - Pereira, António Dias; Chaves, Paula
Background: The risk of esophageal adenocarcinoma (EAC) in non-dysplastic Barrett's esophagus (NDBE) is considered to be approximately 0.3% per year or even lower, according to population-based studies. Data from countries with low EAC incidence are scarce. Our principal aim was to determine the incidence of high-grade dysplasia (HGD) and EAC in NDBE. Our secondary aims were to identify the predictors of progression and to calculate the incidence of HGD/EAC, by using the calculation method for surveillance time in population-based studies. Materials and methods: A cohort of NDBE patients was prospectively followed up. Cases of HGD and EAC (study end points) diagnosed during the first year of follow-up were considered as prevalent. Only cases with an endoscopic surveillance time > 1 year were included in our analysis. Results: We enrolled 331 patients (251 men) in the surveillance program. Their median age was 59 years (interquartile range (IQR): 47–67 years). Their median NDBE length was 3 cm (IQR: 2–4 cm). Of these patients, 80 died during the follow-up (one from EAC) and two were lost to follow-up. After 2284 patient-years of endoscopic follow-up (median surveillance time, 5 years (IQR: 2–10 years)), we found that five cases of HGD and two cases of EAC were diagnosed. The incidence of HGD/EAC was 3.1 cases per 1000 patient-years (95% CI: 1.3–6.0) and that of EAC was 0.9 (95% CI: 0.2–2.9). The incidence of HGD/EAC in short segments (≤ 3 cm) was 0.7 cases per 1000 patient-years (95% CI: 0.3–3.4). The sole variable that we found associated with progression was NDBE length. If the total surveillance time was considered (3537 patient-years), the incidence of HGD and EAC was only slight lower. Conclusions: The incidence of HGD and EAC was very low in NDBE. Therefore, current surveillance guidelines must be reassessed, at least for short-segment BE.